2021
DOI: 10.3389/fpsyg.2021.681569
|View full text |Cite
|
Sign up to set email alerts
|

Dream Activity in Narcoleptic Patients During the COVID-19 Lockdown in Italy

Abstract: Some studies highlighted that patients with narcolepsy type-1 (NT1) experience high lucid dream frequency, and this phenomenon has been associated with a creative personality. Starting from the well-known “pandemic effect” on sleep and dreaming, we presented a picture of dream activity in pharmacologically treated NT1 patients during the Italian lockdown. Forty-three NT1 patients completed a web-survey during Spring 2021 and were compared with 86 matched-controls. Statistical comparisons revealed that: (a) NT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…Similarly, emotional intensity and nightmare distress were lower during the second wave than during the first wave. These results are consistent with the previous literature on pandemic dreams, confirming that the lockdown period (spring 2020) changed oneiric activity provoking a higher dream production and dreams with greater emotional intensity and nightmare distress [7,[12][13][14][15]17]. However, we revealed that during the second wave the emotional valence of dream experience was more negative than during the total lockdown period.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, emotional intensity and nightmare distress were lower during the second wave than during the first wave. These results are consistent with the previous literature on pandemic dreams, confirming that the lockdown period (spring 2020) changed oneiric activity provoking a higher dream production and dreams with greater emotional intensity and nightmare distress [7,[12][13][14][15]17]. However, we revealed that during the second wave the emotional valence of dream experience was more negative than during the total lockdown period.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, stable characteristics, i.e., age and gender modulated the oneiric frequency. Indeed, during lockdown women showed greater self-reported dream frequency [12,13,15], and older adults reported lower dream rates [12,15,17]. In addition, nightmares increased during the Italian lockdown [12].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, changes in the qualitative features of dreams [ 19 , 22 , 23 ] and pandemic-related dream contents [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ] have been described. Different factors seem to influence specific pandemic-related dream changes [ 18 , 19 , 20 , 21 , 22 , 28 , 30 , 31 , 32 ], including modifications of the sleep pattern, characteristics of daily experience, emotional status, and sociodemographic variables.…”
Section: Introductionmentioning
confidence: 99%
“…However, sleep problems were assessed with only two items of the “Duke health profile” [ 18 ] in this study. Another research [ 19 ], aimed at confirming the effects of the lockdown on oneiric activity [ 14 , 20 , 21 ] using a longitudinal evaluation of daily sleep and dream diaries, found greater ease in falling asleep and reduced nocturnal awakenings, dream, and lucid dream recall frequency in an Italian sample during the first week after the confinement (compared with the last week of lockdown). However, possible parallel changes in emotional status were not measured.…”
Section: Introductionmentioning
confidence: 99%